Turning Points of History: Ceausescu's Kids - Alton, Mary Ann (Barna Alper Productions, 1989)
For a generation Romanian women were forced to have babies they didn't want. Nicolae Ceausescu imposed a ban on abortion and birth control and forced every woman of child bearing age to have at least four children. Control over reproduction was strictly enforced. The infant and maternal death rate was high. Thousands babies were born with AIDS. In cases when children were born with mental or physical disabilities, their parents were explicitly encouraged to leave them in the special orphanages. In certain cases, when parental agreement was not easily obtainable, parents were made to believe that their infant was dead while in reality the new-born was transferred to the special "child-care" institution. Plagued by horrifying living conditions and wide-spread abuse, these orphanages were often situated in remote areas of the country, keeping the "embarrassing" sight of disabled children away from public view. The film crew shot much of the footage in such institutions and the result is a shockingly graphic sequence of skeleton-like emaciated and neglected children. Ceausescu's lasting legacy is a generation of unwanted children.
Highly graphic images
Duration: 01:00:00
Keywords: Documentary films